Patients’ experiences with fluctuations in persistent physical symptoms: a qualitative study - Johannes C van der Wouden; Hieke Barends; Ella Walstock; Femke Botman; Anja de Kruif; Nikki Claassen; Tim olde Hartman; Joost Dekker; Henriette van der Horst (BMJ Open)
Objectives To explore patients’ experiences with fluctuations in persistent physical symptoms (PPS) and to understand which factors—from their viewpoint—play a role in these fluctuations.Design Qualitative study using semistructured interviews and thematic content analysis.Setting This qualitative study is part of a multicentre prospective cohort study on the course of PPS. Patients were recruited in general practices and specialised treatment facilities for PPS throughout the Netherlands.Participants Interviews were conducted with a sample of fifteen patients with PPS to explore their experiences with fluctuations in symptom severity.Results We identified three themes in the analysis: (1) patterns in symptom fluctuations (2) perceived causes of symptom exacerbations and (3) Patients’ strategies in gaining control over symptom exacerbations. Daily and weekly fluctuations in symptoms were an important element in patients’ experiences. In particular anticipating on the worsening of symptoms impacted their daily routines and posed various challenges. Symptom exacerbations were attributed to overstepping physical limits and/or the impact of negative emotions. Resigning to physical limits, adjusting ones daily planning, weighing personal needs and learning to say ‘no’ were described as different strategies in gaining control over symptom exacerbations.Conclusions Fluctuations in the severity of symptoms—and in particular daily and weekly symptom exacerbations—are an important element of the symptom experience in patients with PPS and poses various challenges. Patients attributed symptom exacerbation to overstepping physical limits and/or negative emotions. Patients described different strategies in gaining control over symptom exacerbations.